Virtual Cities as Memoryscapes: The Case of Lisbon. - Câmara, Alexandra Gago da (2021)
We argue that virtual recreations of cities a re memoryscapes: by creating the simulacrum of a specific historic moment of the city they establish a way of viewing its past, caused by the subsequent event which changed it (whose future occurrence is always implicit) and configured by the areas and buildings recreated. These virtual recreations also form part of the memory of the city because the memory of its existence was preserved by historic documents and/or because the areas and buildings of the past still exist, even if altered, in the present day city.